ASSESSMENT OF SOIL COMPACTION UNDER DIFFERENT MANAGEMENT REGIMES USING DOUBLE-CYCLE UNIAXIAL COMPRESSION TEST - Víctor Manuel Vaca García; Aurelio Domínguez López; Andrés González Huerta; Edgar Jesús Morales Rosales; Omar Franco Mora; Francisco Gutiérrez Rodríguez (Terra Latinoamericana, 2014)
The impact of wheeled farm machines trafficking on soil compaction has not been well documented in Mexico, particularly in the maize producing area of the Toluca-Atlacomulco Valley, which features a Vertisol soil type. In addition, laboratory measurements are needed that can imitate field conditions is needed to make measurements that are sensitive, reliable and appropriate for monitoring changes in compaction and other physical soil properties while reducing destructive sampling in the field. The objective of this research was to use double-cycle uniaxial compression, penetration resistance and cutting force tests to assess the response of a Vertisol in terms of hardness, cohesiveness and adhesiveness when compacted by wheel traffic in three different types of tillage systems: zero tillage (ZT), minimal tillage (MT) and conventional tillage (CT). The study was conducted in Toluca, State of Mexico, in 2011. Soil samples were collected from the tractor’s wheel track, with three repetitions at two depths. All of the variables were measured using a universal testing machine. For penetration resistance and cutting force tests, standard screwdrivers were used as probes. According to the uniaxial compression test, CT was found to increase soil hardness, relative to the other systems (47% higher on average). MT reported the highest adhesiveness value (0.1 N s-1), but no statistically significant differences in cohesiveness were found among tillage systems. In the ZT system higher penetration resistance was observed in subsoil than in topsoil. MT obtained the maximum cutting force value (54.55 N), while there were no significant differences between other two systems. In these trials the universal testing machine was sensitive enough to detect differences in the soil physical properties of the different tillage systems.